2021
DOI: 10.3390/vaccines9020129
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Receive the COVID-19 Vaccination in China: Application of the Diffusion of Innovations Theory and the Moderating Role of Openness to Experience

Abstract: COVID-19 has caused a devastating impact on public health and made the development of the COVID-19 vaccination a top priority. Herd immunity through vaccination requires a sufficient number of the population to be vaccinated. Research on factors that promote intention to receive the COVID-19 vaccination is warranted. Based on Diffusion of Innovations Theory, this study examines the association between the perceived efficacy of the COVID-19 vaccination, use of social media for COVID-19 vaccine-related informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 54 publications
7
82
1
Order By: Relevance
“…More participants were willing to accept the COVID-19 vaccination at a higher level of effectiveness, with a significant difference of 12.4% between 90% and 95% effectiveness. Increased vaccine acceptance in relation to vaccine effectiveness was found in other studies [ 22 , 23 ], and was related to concerns over vaccine safety [ 24 , 25 ]. The overall acceptance rate of 76.4% and 88.8% for 90% and 95% effectiveness is comparable to the results of a systematic review, where the acceptance rates for most studies among the general population was ≥70% [ 26 ].…”
Section: Discussionmentioning
confidence: 60%
“…More participants were willing to accept the COVID-19 vaccination at a higher level of effectiveness, with a significant difference of 12.4% between 90% and 95% effectiveness. Increased vaccine acceptance in relation to vaccine effectiveness was found in other studies [ 22 , 23 ], and was related to concerns over vaccine safety [ 24 , 25 ]. The overall acceptance rate of 76.4% and 88.8% for 90% and 95% effectiveness is comparable to the results of a systematic review, where the acceptance rates for most studies among the general population was ≥70% [ 26 ].…”
Section: Discussionmentioning
confidence: 60%
“… 3 Kuter et al 32 2021 12,034 Clinical and nonclinical staff CS United States 63.7% Gender (male), age(older), education (more educated), Asian or White, up-to-date on vaccinations, and tested for COVID-19 in the past. 4 Kwok et al 39 2021 1205 Nurses CS China 63% Younger age, more confidence, less complacency and more collective responsibility 5 Lin et al 40 2020 3541 Chinese citizens (≥18 years) CS China 28.7% Perceived benefit, and perceived barriers were found to have the highest significant odds of a definite intention 6 Malik et al 33 2020 672 Adult population CS United States 67% NA 7 Mo et al 41 2021 6922 University students CS China 78.9% Perceived efficacy of vaccination, and use of social media for COVID-19 vaccine-related information. 8 Reiter et al 34 2020 2006 Adults ≥18 years CS United States 69% Recommendation for va...…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the study reported that factors such as perceived risk of COVID-19, 30 , 31 , 34 , 44 , 47 , 50 , 51 , 53 , 58 , 59 , 68–71 trust in healthcare system, 46 , 51 health insurance, 31 , 48 norms, 31 , 65 attitude towards a vaccine, 31 , 55 , 58 perceived benefit of vaccine, 31 , 40 , 46 , 65 , 70 perceived vaccine barriers, 31 , 40 , 70 self-efficacy, 31 up-to-date on vaccinations, 32 being tested for COVID-19 in the past, 32 , 72 responsibility, 39 perceived efficacy of the COVID-19 vaccination, 41 , 47 use of social media for COVID-19 vaccine-related information, 41 recommended for vaccination, 34 political leaning, 34 perceived severity of COVID-19, 34 , 44 , 46 , 70 , 74 perceived effectiveness of a COVID-19 vaccine, 34 , 43 , 59 , 61 belief that vaccination makes them feel less worried about COVID-19, 59 believing in mandatory COVID-19 vaccination, 50 perceived potential vaccine harms, 34 , 42 , 53 , 58 presence of chronic disease, 45 , 48 , 60 previously received an influenza vaccine, 43 , 45 , 47 <...>…”
Section: Discussionmentioning
confidence: 99%
“…6 It is important to note that vaccine hesitancy for newly launched vaccines reduced over time in our study, which has also been observed earlier. 21,22 COVID-19 vaccine uptake, especially among young college students has been explained through diffusion of innovation theory through openness to experience and adoption of descriptive norm. 21 Innovators and early adopters of COVID-19 vaccination could play a role in facilitating its wider acceptance in the medical student community.…”
Section: Discussionmentioning
confidence: 99%